In Vitro Closure Times (PFA-100) Are Different Between Peritoneal Dialysis and Hemodialysis - Gokalp, Cenk; Karadag, Fatma Keklik; Braunisch, Matthias Christoph; Schmaderer, Christoph; Gunay, Emrah; Kiper, Hatice Demet; Tobu, Mahmut; Ustün, Celalettin; Demirci, Meltem Sezis; Ozkahya, Mehmet (Hämostaseologie, 2020)
Introduction Platelet dysfunction is not uncommon in patients with end-stage renal disease (ESRD). Type of renal replacement therapy may have an effect on platelet functions, which has not been well investigated. We evaluated in vitro closure time (CT) differences between peritoneal dialysis (PD) and hemodialysis (HD) patients using platelet function analyzer (PFA-100)and observed a significant difference between these renal replacement therapies.Methods Patients with ESRD undergoing PD (n = 24) or HD (n = 23) for more than 6 months were included. Blood samples for collagen/epinephrine (Col/EPI) and collagen/adenosine diphosphate (Col/ADP) measurements were obtained before HD at a mid-week session for HD patients and at an outpatient control time for PD patients.Results Three of 24 (12.5%) PD patients and 16 of 23 (69.5%) HD patients had prolonged PFA-100 Col/EPI, p< 0.001. Likewise, 4.2% of PD patients and 87.0% of HD patients had prolonged PFA-100 Col/ADP, p< 0.001. Moreover, the median times of PFA-Col/EPI and PFA-100 Col/ADP were significantly lower in PD patients compared with those of HD patients (p< 0.001). Multivariate analysis showed that the type of renal replacement was a risk factor for both elevated PFA-100 Col/ADP and PFA-100 Col/EPI after adjusted for platelets, hematocrit, and urea (p< 0.001).Conclusions The type of renal replacement therapy may have an effect on in vitro CTs; therefore, studies including more patients with long-term follow-up are needed to investigate if the difference has any impact on clinical outcomes.
Keywords: in vitro closure time; hemodialysis; peritoneal dialysis; thrombocyte function; primary hemostasis